KARAKTERISTIK BRIKET DENGAN PENCAMPURAN KULIT BATANG SAGU DAN TEMPURUNG KELAPA - Afna; Pato, Usman; Hamzah, Farida Hanum (Fakultas Pertanian Universitas Riau, 2021)
Sago stem bark and coconut shell contain lignin and cellulose compounds which are quite high and have not been utilized optimally. Therefore this study aimed to obtain the best formulation of the sago stem bark and coconut shell as the main ingredients in making good quality briquette. The research was carried out experimentally using the Completely Randomized Design (CDR) method with 5 treatments and 3 replications. The treatments in this study were P1 (ratio of sago bark charcoal and coconut shell charcoal 90:10), P2 (ratio of sago bark charcoal and coconut shell charcoal 80:20), P3 (ratio of sago bark charcoal and coconut shell charcoal 70:30), P4 (ratio of sago bark charcoal and coconut shell charcoal 60:40), P5 (ratio of sago bark charcoal and coconut shell charcoal 50:50). Data obtained were statically analyzed by analysis of variance (ANOVA) and continued with Duncan’s New Multiple Range Test (DMRT) at level 5%. The results show that the ratio of sago stem bark and coconut shells did not significantly affect moisture, ash and bound carbon contents as well as density, heating value, volatile matter levels and fuel power. The best treatment was P5 (rasio of sago bark charcoal and coconut shell charcoal 50:50) with moisture content 3.67%, ash power 4.54%, volatile matter 1.13%, density power 0.67 g/cm3, bound carbon 90,68%, calorific value 7748.62 cal/g and fuel power 0,0029 g/second.